Crop loss, aetiology and epidemiology of citrus black spot in Ghana - Brentu, F.C.; Oduro, K.A.; Offei, S.K.; Odamtten, G.T.; Vicent, A.; Peres, N.A.; Timmer, L.W. (Springer, 2012)
Citrus Black Spot (CBS), caused by Guignardia citricarpa, was detected for the first time in Ghana and in West Africa. The disease was first observed in the Eastern Region in 1999 with typical disease symptoms including hard spot, virulent spot and false melanose were observed on several citrus species. A survey revealed that the disease has reached epidemic levels in the citrus-producing areas of the Eastern and Ashanti regions and is spreading rapidly within these areas and to other regions of the country. Currently, CBS is the most important fruit disease of citrus in Ghana, causing about 22% crop loss. Although the disease does not cause postharvest decay and the internal quality of the fruit is not affected, significant amounts of blemished fruit are discarded at the markets. Disease incidence and severity was found to be higher on mature than on young citrus trees. Pycnidia were found on fruit with hard spot symptoms, and pycnidia and pseudothecia typical of Guignardia spp. were found on decomposing leaves. Two species, G. citricarpa and G. mangiferae, were isolated from 15% of the samples collected and identified using the Oatmeal Agar test and by PCR with species-specific DNA primers. Isolates of G. citricarpa produced CBS symptoms after 80 to 233 days on 75% of the artificially inoculated young fruit of Valencia Late sweet orange. The fungus was re-isolated from symptomatic, inoculated fruit completing Koch’s postulates. Isolates of the endophyte G. mangiferae did not induce symptoms in the pathogenicity tests. In epidemiological studies, infections were detected from November to February for the minor cropping season and from May to November for the major season. Fruit of Valencia Late sweet orange were susceptible to G. citricarpa infection for up to 7 months after petal fall. Knowledge of the disease cycle in Ghana will improve methods for disease control.
Keywords: Citrus sinensis; Guignardia citricarpa; G. mangeferae; Ceratitis ditissima; West Africa